Facial Fractures Related to Soccer - Secanho, Murilo Sagrbi [UNESP]; Neto, Balduino Ferreira Menezes [UNESP]; Mazzoni, Leticia Perez [UNESP]; Mazzoni, Larissa Perez [UNESP]; Parra, Felipe Lucas [UNESP]; Neto, Aristides Augusto Palhares [UNESP] (Wolters Kluwer, 2021)
Soccer is one of the most popular sports in the world. Despite the concept that soccer is not a violent game, it can lead to several injuries in amateur and professional settings, including facial fractures. Previous studies of facial fractures in soccer were all retrospective and, to date, no prospective studies are available in the literature.The authors performed a comprehensive literature search using the terms soccer AND facial fracture OR craniofacial fracture and football AND facial fracture OR craniofacial fracture and retrieved 693 articles. After applying inclusion and exclusion criteria, 11 articles were included in the present study.A total of 647 patients had suffered facial trauma, with a male-to-female ratio of 63.7:1. The patients' mean age was 27.3 years.The articles reported 670 fractures as follows: 219 (32.7%) in the zygoma, 197 (29.4%) in the nasal bone, 153 (23.6%) in the mandibula, 54 (8.0%) in the orbital wall, 12 (1.8%) in the frontal sinus, 10 (1.5%) in the alveolar bone, 3 (0.4%) in the maxilla, 3 (0.4%) in a Le Fort pattern, and 1 (0.1%) in a naso-orbito-ethmoid (NOE) pattern.Sports are a frequent cause of maxillofacial trauma and are responsible for 9.2% to 33.2% of such injuries. Soccer is a contact sport more associated with lower-limb injuries, but with a significant rate of facial fractures. As soccer is a popular sport played without facial protection and involving high-intensity movements and contact, the prevention of facial fractures related to this sport is crucial to improve the players' safety.
Keywords: Facial fracture; football; soccer